TERJEMAHAN KITAB YAKOBUS DALAM CONTEMPORARY ENGLISH VERSION DAN ALKITAB INDONESIA TERJEMAHAN BARU - Memah, Wine Lisa; Rambing, Rosalina; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ This research entitled â€œThe Translation Book of James in the Contemporary English Version and New Indonesian Translation Bibleâ€ is written to identify, classify and analyze the differences book of James in the Contemporary English Version and New Indonesian Translation Bible. The method used in this research is descriptive method. The data were taken from the book of James based on Contemporary English Version and New Indonesian Translation Bible in terms of personal pronouns, conjunctions, plural and singular forms, vocabularies, and tenses by using the Larsonâ€™s (1984) and Ladoâ€™s (1971) theory. The book of James in the Contemporary English Version and New Indonesian Translation Bible has 30 differences in terms of grammatical structure and lexical meanings. Both of the books have 5 chapters consist of 107 verses. There are 169 sentences in the book of James in Contemporary English Version but the book of James in the New Indonesian Translation Bible only has 127 sentences. The differences are most commonly found by the writer are the use of conjunctions and plural and singular forms.Â Keywords: Translation, Contrastive, Book of James.